Posisi Kurikulum Pendidikan Indonesia dalam Pendidikan Multikultural - Rahman, Arif; Berliyana, Adhe Sukma; Iklima, Iklima; Rahma, Anisa Nuraida; Fitriah, Januari; Jannah, Fathul (ALSYS, 2022)
Indonesia consists of various tribes, races, ethnicities and religions. In this diversity, multicultural education is needed to be implemented in people's lives. To be able to tolerate each other, take responsibility and to be able to help each other among others. Not to hate each other or complain to each other. Religion is expected to be a complement and can also complement each other so that it can become strong and also close. Circumstances like this can shape the character of the Indonesian nation to be more formed. As Indonesian people, we should be able to take care of each other so that there are no disputes that can lead to conflict.